ОСОБЛИВОСТІ РІВНІВ ЗАПАЛЬНИХ МАРКЕРІВ У ХВОРИХ НА ГІПЕРТОНІЧНУ ХВОРОБУ ІІ СТАДІЇ: ФОКУС НА ОРГАНИ-МІШЕНІ (World Science, 2020)
Arm of our study was to evaluate the levels of inflammatory markers in patients with arterial hypertension stage II with depending on the numbers of affected target organs. Levels of C-reactive protein and alpha-tumor necrosis factor were significantly higher in patients with arterial hypertension than in healthy individuals. An involvement of more target organs damages was associated with greater inflammatory activation in hypertensive patients. The levels of C-reactive protein and α-tumor necrosis factor had significant correlation relationship with the markers of target organ damage.